Risk Factors for Bullying Victimization in Children with Neurofibromatosis Type 1 (NF1) - Peter L. Stavinoha; Cody Solesbee; Susan M. Swearer; Steven Svoboda; Laura J. Klesse; Alice Ann Holland (MDPI AG, 2021)
Neurofibromatosis type 1 (NF1) is an autosomal disorder associated with numerous physical stigmata. Children with NF1 are at known risk for attention-deficit/hyperactivity disorder (ADHD), academic struggles, and significant social difficulties and adverse social outcomes, including bullying victimization. The primary aim of this study was to identify risk factors associated with bullying victimization in children with NF1 to better inform clinicians regarding targets for prevention and clinical intervention. Children and a parent completed questionnaires assessing the bully victim status, and parents completed a measure of ADHD symptoms. Analyses were completed separately for parent-reported victimization of the child and the child's self-report of victimization. According to the parent report, results suggest ADHD symptoms are a significant risk factor for these children being a target of bullying. Findings for academic disability were not conclusive, nor were findings related to having a parent with NF1. Findings indicate the need for further research into possible risk factors for social victimization in children with NF1. Results provide preliminary evidence that may guide clinicians working with children with NF1 and their parents in identifying higher-risk profiles that may warrant earlier and more intensive intervention to mitigate later risk for bullying victimization.